Immunogenic cell death triggered by impaired deubiquitination in multiple myeloma relies on dysregulated type I interferon signaling - Waad Sadiq, Zeinab; Brioli, Annamaria; Al-Abdulla, Ruba; Çetin, Gonca; Schütt, Jacqueline; Murua Escobar, Hugo; Krüger, Elke; Ebstein, Frédéric (Frontiers in Immunology, 2023)
Proteasome inhibition is first line therapy in multiple myeloma (MM). The immunological potential of cell death triggered by defects of the ubiquitin-proteasome system (UPS) and subsequent perturbations of protein homeostasis is, however, less well defined. In this paper, we investigated the protein homeostasis disruptors bortezomib (BTZ), ONX0914, RA190 and PR619 for their ability to induce immunogenic cell death (ICD) in various MM cell lines and primary patient samples. Our data show that while BTZ treatment triggers sterile type I interferon (IFN) responses, exposure of the cells to ONX0914 or RA190 was mostly immunologically silent. Interestingly, inhibition of protein de-ubiquitination by PR619 was associated with the acquisition of a strong type I IFN gene signature which relied on key components of the unfolded protein and integrated stress responses including inositol-requiring enzyme 1 (IRE1), protein kinase R (PKR) and general control nonderepressible 2 (GCN2). The immunological relevance of blocking de-ubiquitination in MM was further reflected by the ability of PR619-induced apoptotic cells to facilitate dendritic cell (DC) maturation via type I IFN-dependent mechanisms. Altogether, our findings identify de-ubiquitination inhibition as a promising strategy for inducing ICD of MM to expand current available treatments.